Coronaviruses resistant to a 3C-like protease inhibitor are attenuated for replication and pathogenesis, revealing a low genetic barrier but high fitness cost of resistance - Xufang Deng (2018)
© 2014, American Society for Microbiology. Viral protease inhibitors are remarkably effective at blocking the replication of viruses such as human immunodeficiency virus and hepatitis C virus, but they inevitably lead to the selection of inhibitor-resistant mutants, which may contribute to ongoing disease. Protease inhibitors blocking the replication of coronavirus (CoV), including the causative agents of severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS), provide a promising foundation for the development of anticoronaviral therapeutics. However, the selection and consequences of inhibitor-resistant CoVs are unknown. In this study, we exploited the model coronavirus, mouse hepatitis virus (MHV), to investigate the genotype and phenotype of MHV quasispecies selected for resistance to a broad-spectrum CoV 3C-like protease (3CLpro) inhibitor. Clonal sequencing identified single or double mutations within the 3CLpro coding sequence of inhibitor-resistant virus. Using reverse genetics to generate isogenic viruses with mutant 3CLpros, we found that viruses encoding double-mutant 3CLpros are fully resistant to the inhibitor and exhibit a significant delay in proteolytic processing of the viral replicase polyprotein. The inhibitor-resistant viruses also exhibited postponed and reduced production of infectious virus particles. Biochemical analysis verified double-mutant 3CLpro enzyme as impaired for protease activity and exhibiting reduced sensitivity to the inhibitor and revealed a delayed kinetics of inhibitor hydrolysis and activity restoration. Furthermore, the inhibitor-resistant virus was shown to be highly attenuated in mice. Our study provides the first insight into the pathogenicity and mechanism of 3CLpro inhibitor-resistant CoV mutants, revealing a low genetic barrier but high fitness cost of resistance.